Annual 10Be concentrations from Lakes Tiefer See and Czechowskie AD1983-2009 - Czymzik, Markus; Muscheler, Raimund; Brauer, Achim; Adolphi, Florian; Ott, Florian; Kienel, Ulrike; Dräger, Nadine; Słowiński, Michał; Aldahan, Ala; Possnert, Göran (Supplement to: Czymzik, M et al. (2015): Solar cycles and depositional processes in annual 10Be from two varved lake sediment records. Earth and Planetary Science Letters, 428, 44-51, https://doi.org/10.1016/j.epsl.2015.07.037, 2015)
Beryllium 10 concentrations (10Becon) were measured at annual resolution from varved sediment cores of Lakes Tiefer See (TSK) and Czechowskie (JC) for the period 1983-2009 (~solar cycles 22 and 23). Calibrating the 10Becon time-series against complementing proxy records from the same archive as well as local precipitation and neutron monitor data, reflecting solar forced changes in atmospheric radionuclide production, allowed (i) identifying the main depositional processes and (ii) evaluating the potential for solar activity reconstruction. 10Becon in TSK and JC sediments are significantly correlated to varying neutron monitor counts (TSK: r=0.5, p=0.05, n=16; JC: r=0.46, p=0.03, n=22). However, the further correlations with changes in organic carbon contents in TSK as well as varying organic carbon and detrital matter contents in JC point to catchment specific biases in the 10Becon time-series. In an attempt to correct for these biases multiple regression analysis was applied to extract an atmospheric 10Be production signal (10Be atmosphere). To increase the signal to noise ratio a 10Be composite record (10Be composite) was calculated from the TSK and JC 10Be atmosphere time-series. 10Becomposite is significantly correlated to variations in the neutron monitor record (r=0.49, p=0.01, n=27) and matches the expected amplitude changes in 10Be production between solar cycle minima and maxima. This calibration study on 10Be from two sites indicates the large potential but also, partly site-specific, limitations of 10Be in varved lake sediments for solar activity reconstruction.